Bupivacaine‐induced cellular entry of QX‐314 and its contribution to differential nerve block. (January 2014) - Brenneis, C; Kistner, K; Puopolo, M; Jo, S; Roberson, DP; Sisignano, M; Segal, D; Cobos, E J; Wainger, B J; Labocha, S; Ferreirós, N; von, C; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose Selective nociceptor fibre block is achieved by introducing the cell membrane impermeant sodium channel blocker lidocaine N‐ethyl bromide (QX‐314) through transient receptor potential V1 (TRPV1) channels into nociceptors. We screened local anaesthetics for their capacity to activate TRP channels, and characterized the nerve block obtained by combination with QX‐314. Experimental Approach We investigated TRP channel activation in dorsal root ganglion (DRG) neurons by calcium imaging and patch‐clamp recordings, and cellular QX‐314 uptake by MS. To characterize nerve block, compound action potential (CAP) recordings from isolated nerves and behavioural responses were analysed. Key Results Of the 12 compounds tested, bupivacaine was the most potent activator of ruthenium red‐sensitive calcium entry in DRG neurons and activated heterologously expressed TRPA1 channels. QX‐314 permeated through TRPA1 channels and accumulated intracellularly after activation of these channels. Upon sciatic injections, QX‐314 markedly prolonged bupivacaine's nociceptive block and also extended (to a lesser degree) its motor block. Bupivacaine's blockade of C‐, but not A‐fibre, CAPs in sciatic nerves was extended by co‐application of QX‐314. Surprisingly, however, this action was the same in wild‐type, TRPA1‐knockout and TRPV1/TRPA1‐double knockout mice, suggesting a TRP‐channel independent entry pathway. Consistent with this, high doses of bupivacaine promoted a non‐selective, cellular uptake of QX‐314. Conclusions and Implications Bupivacaine, combined with QX‐314, produced a long‐lasting sensory nerve block. This did not require QX‐314 permeation through TRPA1, although bupivacaine activated these channels. Regardless of entry pathway, the greatly extended duration of block produced by QX‐314 and bupivacaine may be clinically useful.